2010
DOI: 10.1152/japplphysiol.00804.2009
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary activation failure contributes more to plantar flexor weakness than antagonist coactivation and muscle atrophy in chronic stroke survivors

Abstract: The contributions of nervous system muscle activation and muscle atrophy to poststroke weakness have not been evaluated together in the same subject. Maximal voluntary contraction (MVC) torque, voluntary activation (twitch interpolation), and electromyographic (EMG) amplitude were determined bilaterally in the plantar flexors of seven chronic stroke survivors (40-63 yr, 24-51 mo poststroke). Volumes of the plantar flexor muscles were determined bilaterally with magnetic resonance imaging (MRI). The mean (±SD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 50 publications
12
94
2
Order By: Relevance
“…Although increases in antagonist coactivation have been observed poststroke (Trumbower et al 2010), it is unlikely that antagonist coactivation played a role in the observed saturation in firing profiles in the current study, as coactivation ratios of the antagonist elbow extensor and elbow flexor muscles were similar across muscle types during the voluntary ramp contractions. This agrees with previous findings in which antagonist coactivation did not contribute to muscle weakness poststroke (Klein et al 2010).…”
Section: Non-pic-based Mechanisms For Saturation In Motor Unit Firingsupporting
confidence: 93%
See 2 more Smart Citations
“…Although increases in antagonist coactivation have been observed poststroke (Trumbower et al 2010), it is unlikely that antagonist coactivation played a role in the observed saturation in firing profiles in the current study, as coactivation ratios of the antagonist elbow extensor and elbow flexor muscles were similar across muscle types during the voluntary ramp contractions. This agrees with previous findings in which antagonist coactivation did not contribute to muscle weakness poststroke (Klein et al 2010).…”
Section: Non-pic-based Mechanisms For Saturation In Motor Unit Firingsupporting
confidence: 93%
“…Firing rate slopes that were Յ0.5 pps/s, despite increasing force, were considered as impaired rate modulation. Because the force profile during the voluntary ramp contractions may not adequately represent the descending drive equally in the different muscle types (Fellows et al 1994;Klein et al 2010;Madhaven et al 2011), we performed a secondary analysis in which we used the firing rate profile of the higher-threshold unit instead of the peak force as an index of the descending drive. Furthermore, because maximal firing rates may be variable poststroke (Hu et al 2012), we used the peak of the smoothed lower-threshold unit's firing rate profile instead of the average of three spikes surrounding the first maximum firing rate as the start of the saturation in firing rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of central nervous system lesion, like stroke, the plantar flexor muscles are more prone to activation failure than the proximal muscles (i.e. quadriceps) (Klein et al, 2010). Specifically, the behaviour of the soleus as a postural muscle may reveal postural control dysfunction more evidently, since uniarticular muscles are thought to be more affected by central influences than by peripheral influences (Kautz et al, 2005).…”
Section: -Postural Control Dysfunction In the Ipsilesional Sidementioning
confidence: 99%
“…Electrodes were placed in muscles midbelly according to anatomical references (Cheng et al 2004;Klein et al 2010). The ground electrodes were placed over each patella.…”
Section: Preparationmentioning
confidence: 99%